Institutional Readiness for Social Resilience Budget Tagging: Lessons from Climate Budget Tagging in Indonesia - Andi Faisal (Universitas Negeri Makassar, 2026)
This article analyzes Indonesia's institutional readiness to implement Social Resilience Budget Tagging (SRBT) by using the experience of Climate Budget Tagging (CBT) as an analytical mirror. Through an institutional analysis approach based on literature and policy documents, the study evaluates three readiness dimensions: regulatory capacity (legal and policy frameworks), normative capacity (budgeting norms and procedures), and cognitive capacity (conceptual and technical understanding of officials). The study finds that Indonesia possesses a relevant institutional foundation through CBT implementation within the KRISNA system, yet faces four significant readiness gaps: (1) the absence of a legal framework that explicitly mandates social resilience-based tagging; (2) uneven technical capacity across ministries and regions; (3) an institutional incentive system that does not yet support substantive tagging behavior; and (4) the absence of a credible independent verification mechanism. The article formulates a four-layer SRBT institutional readiness framework — legal, procedural, capacity, and incentive — and proposes a realistic phased implementation pathway based on lessons from Indonesia's CBT trajectory. Implications for public finance system reform and future research are explicitly discussed.